Rapid thrombosis of middle cerebral artery aneurysm after subarachnoid haemmorhage. (9th April 2013) - Mathur, Tarun; Srivastava, Trilochan; Mittal, R S; Tejwani, Shankar; Raghavendra, B S; Jain, Rahul
Abstract : Spontaneous thrombosis of intracranial aneurysm is a rare event but is frequent after subarachnoid haemorrhage (SAH) and in fusiform or giant saccular aneurysms. We report a case of a 20-year-old man presenting with SAH due to rupture of a giant aneurysm of the middle cerebral artery. Initial CT angiography (CTA) revealed partially thrombosed MCA aneurysm but digital subtraction angiography performed 3 days later revealed complete occlusion of the aneurysm. Rapid thrombosis of aneurysm within 3 days has not been reported in literature so far.